2019
DOI: 10.3390/app9235238
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Cement and By-Product Petrit T in Soil Stabilization

Abstract: This study presents a comparison between the effectiveness of adding low binder amounts of industrial by-product Petrit T as well as cement to modify and improve fine-grained soil. Binder amount was added by soil dry weight; cement at 1%, 2%, 4% and 7% and Petrit T at 2%, 4% and 7%. The unconfined compressive strength (UCS) was used as an indicator of soil strength. In addition, the consistency limits, laser particle size analysis, and pH tests were also conducted on the treated soil. The samples were cured at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
(90 reference statements)
1
11
0
Order By: Relevance
“…Conversely, the strain decreased from 2.58% for untreated to 2.08%, 1.56%, 1.37%, and 1.19% for 3%, 6%, 9%, and 12% cement content within 7 days curing. The results obtained for the ductility change with increasing cement and curing time in this research were compatible with [2,70,82,100] in that the authors indicated higher brittleness for high cement content and more curing time. Similarly, in the current study, the ductility changes of a specimen mixed with 3% cement, with a curing time, were not considerable, whereas the ductility significantly decreased for 6%, 9%, and 12% cement.…”
Section: Unconfined Compressive Strengthsupporting
confidence: 87%
See 4 more Smart Citations
“…Conversely, the strain decreased from 2.58% for untreated to 2.08%, 1.56%, 1.37%, and 1.19% for 3%, 6%, 9%, and 12% cement content within 7 days curing. The results obtained for the ductility change with increasing cement and curing time in this research were compatible with [2,70,82,100] in that the authors indicated higher brittleness for high cement content and more curing time. Similarly, in the current study, the ductility changes of a specimen mixed with 3% cement, with a curing time, were not considerable, whereas the ductility significantly decreased for 6%, 9%, and 12% cement.…”
Section: Unconfined Compressive Strengthsupporting
confidence: 87%
“…demonstrate that compressive strength was enhanced with cement content and curing time, the effectiveness of 3% cement was not significant. This behavior could be attributed to the low pH value, whereby the cement could not improve soil strength effectively at a pH value smaller than 12.4 [82]. The UCS results in Figure 7 show that the 6% cement was adequate for stabilizing the lateritic soil to achieve a minimum UCS of 0.8 MPa, according to Malaysia Public Works Department (MPWD) standards.…”
Section: Unconfined Compressive Strengthmentioning
confidence: 97%
See 3 more Smart Citations